2013
DOI: 10.1093/brain/awt343
|View full text |Cite
|
Sign up to set email alerts
|

Efficient mitochondrial biogenesis drives incomplete penetrance in Leber’s hereditary optic neuropathy

Abstract: The mechanisms of incomplete penetrance in Leber’s hereditary optic neuropathy are elusive. Giordano et al. show that mitochondrial DNA content and mitochondrial mass are both increased in tissues and cells from unaffected mutation carriers relative to affected relatives and control individuals. Upregulation of mitochondrial biogenesis may represent a therapeutic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
204
0
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 240 publications
(249 citation statements)
references
References 59 publications
23
204
0
8
Order By: Relevance
“…A more favourable final visual outcome was observed for all three genotypes in our childhood-onset LHON cohort compared with previously published figures (m.3460G>A: 14% vs 55%–96%; m.11778G>A: 45% vs 73%–98%; and m.14484T>C mutation: 6% vs 30%–50% of eyes achieving a BCVA <0.1) 1 6 8 20 21. Mitochondrial turnover is implicated in the pathogenesis of LHON, both mitochondrial biogenesis and mitophagy being increased in fibroblasts of patients with LHON 23 24. The known age-related decline in mitophagy, and hence presumably mitochondrial biogenesis, may underlie this difference from adult disease 25…”
Section: Discussionsupporting
confidence: 68%
“…A more favourable final visual outcome was observed for all three genotypes in our childhood-onset LHON cohort compared with previously published figures (m.3460G>A: 14% vs 55%–96%; m.11778G>A: 45% vs 73%–98%; and m.14484T>C mutation: 6% vs 30%–50% of eyes achieving a BCVA <0.1) 1 6 8 20 21. Mitochondrial turnover is implicated in the pathogenesis of LHON, both mitochondrial biogenesis and mitophagy being increased in fibroblasts of patients with LHON 23 24. The known age-related decline in mitophagy, and hence presumably mitochondrial biogenesis, may underlie this difference from adult disease 25…”
Section: Discussionsupporting
confidence: 68%
“…There is increasing evidence in in vitro studies and animal models that increased mitochondrial biogenesis might be beneficial in many mitochondrial diseases. Interestingly, a recent observation suggested that increased mitochondrial content influences incomplete penetrance in LHON patients and that mitochondrial biogenesis could be used as a therapeutic strategy in this group of patients (44). The biological pathway that controls mitochondrial biogenesis is complex and relies mostly on the PPAR γ coactivator 1α (PGC1α).…”
Section: Emerging Therapiesmentioning
confidence: 99%
“…The idea that mitochondrial biogenesis is critical to determine the phenotypic outcome of disease has been boosted by the recent observation that increased mitochondrial content protects non-manifesting carriers of the LHON mutations. This can partly explain the incomplete penetrance of the disease and opens the possibility to stimulate mitochondrial biogenesis as a therapeutic strategy for LHON [16].…”
Section: Increasing Mitochondrial Biogenesismentioning
confidence: 99%